Vitamin E deficiency depressed fish growth, disease resistance, and the immunity and structural integrity of immune organs in grass carp (Ctenopharyngodon idella): Referring to NF-κB, TOR and Nrf2 signaling. Issue 60 (January 2017) - Pan, Jia-Hong; Feng, Lin; Jiang, Wei-Dan; Wu, Pei; Kuang, Sheng-Yao; Tang, Ling; Zhang, Yong-An; Zhou, Xiao-Qiu; Liu, Yang
Abstract: This study investigated the effects of dietary vitamin E on growth, disease resistance and the immunity and structural integrity of head kidney, spleen and skin in grass carp ( Ctenopharyngodon idella ). The fish were fed six diets containing graded levels of vitamin E (0, 45, 90, 135, 180 and 225 mg/kg diet) for 10 weeks. Subsequently, a challenge test was conducted by injection of Aeromonas hydrophila . The results showed that compared with optimal vitamin E supplementation, vitamin E deficiency caused depressed growth, poor survival rates and increased skin lesion morbidity in grass carp. Meanwhile, vitamin E deficiency decreased lysozyme and acid phosphatase activities, complement component 3 and complement component 4 contents in the head kidney, spleen and skin of grass carp ( P < 0.05). Moreover, vitamin E deficiency down-regulated antimicrobial peptides (Hepcidin, liver-expressed antimicrobial peptide-2A, -2B, β-defensin), IL-10, TGFβ1, IκBα, TOR and S6K1 mRNA levels ( P < 0.05) and up-regulated IL-1β, IL-6, IL-8, IFN-γ2 and TNFα, NF-κB p65, IKKα, IKKβ and 4EBP1 (not in the head kidney) mRNA levels ( P < 0.05). In addition, vitamin E deficiency caused oxidative damage, decreased superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT) and glutathione reductase (GR) activities, and down-regulated the mRNA levels of antioxidant enzymes and signaling molecules Nrf2 ( P < 0.05). Vitamin E deficiency also induced apoptosis by up-regulating capase-2, -3, -7, and -8 mRNA levels in the head kidney, spleen and skin of grass carp. In conclusion, this study indicated that dietary vitamin E deficiency depressed fish growth, impaired the immune function and disturbed the structural integrity of the head kidney, spleen and skin in grass carp, but optimal vitamin E supplementation can reverse those negative effects in fish. The optimal vitamin E requirements for young grass carp (266.39–1026.63 g) to achieve optimal growth performance and disease resistance based on the percent weight gain (PWG) and skin lesion morbidity were estimated to be 116.2 and 130.9 mg/kg diet, respectively. Meanwhile, based on immune indicator (LA activity in the head kidney) and antioxidant indicator (protection of spleen against MDA), the optimal vitamin E requirements for young grass carp were estimated to be 123.8 and 136.4 mg/kg diet, respectively. Highlights: Vitamin E deficiency depressed the immunity of head kidney, spleen and skin. Vitamin E deficiency aggravated the inflammatory response. Vitamin E deficiency decreased head kidney, spleen and skin antioxidant capacity. Vitamin E deficiency induced head kidney, spleen and skin apoptosis. Vitamin E regulated signaling molecules NF-κB, TOR and Nrf2 mRNA expression.